Contribuições para a transformação das práticas escolares: racionalidade comunicativa em Habermas e dialogicidade em Freire - Gabassa, Vanessa (Universidade Federal de São Carlos, 2007)
The thematic of this paper is based on the concept of dialogical action by Paulo Freire as well as rationality and communicative action by Habermas. Its purpose was fundamentally to analyze the concept of dialogue based on Freire s works and likewise the concept of communicative action based on Habermas s works: to highlight each author s specificities as well as the convergence of ideas from the works which were studied, and also to verify how technical rationality can be reconsidered according to communicative action and dialogical action in order to build a school which is both effective for and with everyone. Based on such aims, the study was conducted by the following research question: Which elements does the concept of communicative action by Habermas and dialogical action by Freire provide in order to have technical rationality reconsidered from these two types of action with the purpose of building a school which is both effective for and with everyone? In order to answer this question, a bibliographical and exploratory research was developed based on the reading of several works by both authors with the purpose of elaborating a text capable of answering that question by having summaries and bibliographical files as main sources. The school context commanded by technical rationality was also explored. Likewise, aspects of modernity and neoliberalism were approached in order to contextualize the study proposed. The history of the reason was overlooked from its birth in philosophy up to its comprehension in social sciences with the attempt of revising the object of study. Furthermore, the research was focused on Habermas and Freire s works by contrasting their ideas as well as by showing their agreements and relating their proposals to the rationality question which is present in the scopes of socialization, teaching and school administration. From the studies proposed, the elements of truth, veracity and character posture pointed by Habermas in order to achieve communicative action, as well as the elements love, hope, humility, trustfulness, faith in the world and in people and the critical thinking of Freire were highlighted as being requirements for the establishment of a true and liberating dialogue. In addition, the way they see the world and history shows that the human being is understood as being a historic subject, provided with language skills and actions and, therefore, capable of changing his world, which is also historic and, consequently, trained and not determined though. Through this work, it was possible to evaluate that the elements brought by Freire and Habermas can help on developing a solidarity environment in the schools, which would replace competitiveness and individualism, and also help on promoting the type of teaching on which educators and students can teach and learn at the same time, by building together their learning contents: a school at which the administration is effectively democratic, built both with and for everyone.
Keywords: Sociologia educacional; Ação comunicativa; Dialogicidade; CIENCIAS HUMANAS::EDUCACAO